Education Systems of Indonesia and South Korea: Geopolitics, Structure, and Educational Environment - Fariz, Exzan Abdi; Susanti, Retno; Safitri, Erna Retna; Gulo, Fakhili (Universitas Pahlawan Tuanku Tambusai, 2024)
This study compares the education systems in Indonesia and South Korea, focusing on compulsory education policies, curriculum, learning methods, and academic pressure. South Korea emphasizes academic achievement, especially university entrance exams, and high use of technology in learning. Meanwhile, Indonesia, through the Independent Curriculum, focuses more on developing student potential, character education, and social awareness. This study uses a qualitative literature review method, analyzing various sources such as academic journals and research reports related to the education systems of both countries. Literature analysis was conducted to explore the geopolitical aspects, education structure, and academic environment of South Korea and their comparisons with Indonesia. The main focus is on education policies, technology implementation, and parental involvement in education. The study results indicate that Indonesia can adopt some of South Korea's approaches, such as better technology integration in learning and increasing the role of parents. The data were analyzed using structured content analysis techniques, which allowed researchers to identify key themes and conclude similarities and significant differences between the two education systems. This study is expected to provide valuable insights for education reform in Indonesia, especially related to improving the quality of education through technology